La expresión verbal de las emociones negativas: el caso del insulto - Lisowska, Monika (AMU Press, 2010)
An insult is one of the cases of verbal aggression and undoubtedly it is an everyday life phenomenon. Insulting is a display of direct aggression which arises from anger and aims at the effect on the recipient’s mind. The act of abuse on the other hand, is conditioned by multiple factors. Its success depends, for example, on the knowledge of culture to which the recipient of an insult belongs. Despite the fact that an insult is a cultural phenomenon, i.e. dependent on a particular culture, the mechanism of abuse itself is identical in the entire world. Generally, it is possible to determine a list of universal human disabilities which are subject to insults as well as a universal list of topic areas of insulting expressions.
Keywords: speech acts; insults; semantic universals; verbal aggression